Determinants in customers' satisfaction towards quality of the Ar-Rahnu service provided : case study in Kluang, Johor / Norhazwani Ramli - Ramli, Norhazwani (Faculty of Business Management, 2015)
The purpose of this study is to analyze the direction of causation between exchange rate and selected macroeconomics variables. In order to assess whether there is any potential impact between the variables, a Granger-causality analysis has been carried out to test the impact. It is to clarify how this variable factors and exchange rate movement impact each other. Unites State is taken as a base country to measure the exchange rate movement. The conclusion that can be drawn are exchange rate can predict the movements of industrial production and inflation rate but not vice versa. However, the reverse causation happen at the other lags between inflation rate to exchange rate. Another two variables, money supply and unemployment rate, the results also indicate the unidirectional causality where the causal relationship exist between these two variables towards exchange rate but not vice versa.